The role of accountability in the implementation of the curriculum policy (2013) in secondary school - Salsabilah, Salsabilah (Journal of Strategy and Transformation in Educational Management, 2024)
This study aims to examine the role of accountability in encouraging the implementation of the 2013 Curriculum Policy in secondary schools. This study uses a qualitative approach to the case study method. Data were collected through interviews, observations, and documentation from four secondary schools in Makassar City that implemented the 2013 curriculum. The results show that accountability is vital in encouraging the implementation of the 2013 Curriculum Policy in secondary schools. Accountability can be vertical accountability, which includes the relationship between the school and the board, and horizontal accountability, which includes the relationship between the school and the community. Vertical accountability can facilitate the implementation of the 2013 Curriculum Policy through government monitoring, guidance and evaluation mechanisms. Horizontal accountability can contribute to implementing the 2013 Curriculum Policy through school participation, transparency, and feedback mechanisms. This study recommends that the government increase the capacity and commitment of schools to implement the 2013 curriculum by supporting resources, tools, and incentives. The study also recommends that schools increase community involvement and confidence in implementing the 2013 curriculum by providing information, communication, and consultation.